Effect of Acute, Subacute, and Repeated Exposure to High Altitude (5050 m) on Psychomotor Vigilance - Pun, Matiram; Hartmann, Sara E.; Furian, Michael; Dyck, Adrienna M.; Muralt, Lara; Lichtblau, Mona; Bader, Patrick R.; Rawling, Jean M.; Ulrich, Silvia; Bloch, Konrad E.; Poulin, Marc J. (Frontiers in Physiology, 2018)
OBJECTIVE High altitude hypoxia may affect cognitive performance and sleep quality. Further, vigilance is reduced following sleep deprivation. We investigated the effect on vigilance, actigraphic sleep indices and their relationships with acute mountain sickness (AMS) during very high altitude (HA) exposure, acclimatization, and re-exposure. METHODS Twenty-one healthy altitude-naive individuals (25±4 years; 13 females) completed two cycles of altitude exposure separated by 7 days at low altitude (LA, 520m). Participants slept at 2900m and spent the daytime at HA, (5050m). We report acute altitude exposure on Day 1 (LA vs. HA1) and after 6 days of acclimatization (HA1 vs. HA6). Vigilance was quantified by reaction speed in the 10-minute psychomotor vigilance test (PVT-RS). AMS was evaluated using the Environmental Symptoms Questionnaire Cerebral Score (AMS-C score). Nocturnal rest/activity was recorded to estimate sleep duration using actigraphy. RESULTS In Cycle 1, PVT-RS was slower at HA1 compared to LA (4.1±0.8 vs 4.5±0.6 s-1, respectively, p=0.029), but not at HA6 (4.6±0.7; p>0.05). In Cycle 2, PVT-RS at HA1 and HA6 were not different from LA (p>0.05) and significantly greater than corresponding values in Cycle 1. In both cycles, AMS scores were higher at HA1 than at LA and HA6 (p<0.05). Estimated sleep durations (TST) at LA, 1st and 5th nights were 431.3±28.7, 418.1±48.6 and 379.7±51.4 minutes, respectively in Cycle 1 and they were significantly reduced during acclimatization exposures (LA vs 1st night, p>0.05; LA vs 5th night, p=0.012 and 1st vs 5th night, p=0.054). LA, 1st and 5th nights TST in Cycle 2 were 477.5±96.9, 430.9±34 and 341.4±32.2, respectively and we observed similar deteriorations in TST as in Cycle 1 (LA vs 1st night, p>0.05, LA vs 5th night, p=0.001 and 1st vs 5th night, p<0.0001).. At HA1, subjects who reported higher AMS-C scores exhibited slower PVT-RS (r=-0.56; p<0.01). Subjects with higher AMS-C scores took longer time to react to the stimuli during acute exposure (r=0.62, p<0.01). CONCLUSIONS Acute exposure to HA reduces the PVT-RS. Altitude acclimatization over 6 days recovers the response-speed and prevents impairments during subsequent altitude re-exposure after one week spent near sea level.